2015
DOI: 10.4048/jbc.2015.18.4.313
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dairy Intake and Breast Cancer in Western and Asian Populations: A Systematic Review and Meta-Analysis

Abstract: PurposeTo date, studies investigating the association between dairy consumption and breast cancer in women have produced conflicting results. As diet is an important, modifiable factor affecting cancer development, the aim of this study was to examine the association between dairy consumption and breast cancer risk.MethodsPubMed, Embase, and Cochrane Library databases were searched with a priority for prospective cohort studies. Case-control studies were also considered in case of the absence of a cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 29 publications
(29 reference statements)
3
59
1
1
Order By: Relevance
“…Due to potential bias in the design and the lack of control for known confounders, it is impossible to conclude about the relationship with dairy intake. Also, these findings are in contrast with the additional literature suggesting no or an inverse association between dairy intake and risk of breast cancer (74, 75), ovarian cancer (83, 91), and lung cancer (84, 85). …”
Section: Cancercontrasting
confidence: 99%
See 1 more Smart Citation
“…Due to potential bias in the design and the lack of control for known confounders, it is impossible to conclude about the relationship with dairy intake. Also, these findings are in contrast with the additional literature suggesting no or an inverse association between dairy intake and risk of breast cancer (74, 75), ovarian cancer (83, 91), and lung cancer (84, 85). …”
Section: Cancercontrasting
confidence: 99%
“…In accordance with a meta-analysis from 2011 on prospective cohort studies (74), a recent meta-analysis by Zang et al (75), however, suggested that a high (>600 g/d) and modest (400–600 g/d) dairy intake was associated with a reduced risk of breast cancer (10% and 6%, respectively) compared with a low dairy intake (<400 g/d). Within dairy subgroups, particularly yoghurt and low-fat dairy were found to be inversely associated with the risk of developing breast cancer.…”
Section: Cancermentioning
confidence: 80%
“…Dietary patterns are likely to vary between populations, because of geographic characteristics and cultural differences in food habits, preferences, and availability [125]. Several studies investigating dietary patterns and breast cancer risk have documented an inverse association with a prudent/low fat dietary pattern, which includes the high intake of vegetables, fruits, whole grains, and fish [110, 111, 124, 126], and a positive association with the less healthy Western diet, which is generally characterized by large quantities of red meat, refined grains, potatoes, and fat [127]. …”
Section: Dietary Factors and Nutrition In Breast Cancer Riskmentioning
confidence: 99%
“…A case-control study indicated that a diet characterized by a high consumption of milk is associated with a lower risk for breast cancer among both pre-and postmenopausal women in China [33]. Meta-analyses reported that dairy product consumption was inversely associated with the risk for breast cancer, and this effect varied across types of dairy products [20,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiologic studies have examined the association between consumption of milk and dairy products and the risk for breast cancer [17][18][19]. However, the association between different types of milk and dairy products and risk for breast cancer yield inconsistent results, as only a few studies have shown reduced risks for breast cancer [20][21][22]. Moreover, the findings may vary by the types of dairy products.…”
Section: Introductionmentioning
confidence: 99%